Pemilihan Produk Batik Tulis menggunakan Metode Analytical Hierarchy Process: Studi pada Konsumen Batik Tulis di Madiun - Tifani Karina (Jurnal Ilmu Manajemen, 2022)
The purpose of this study was to determine the criteria used to determine the order of priority in the assessment and selection of batik products. This type of research is quantitative. The sample of this research is 60 batik buyers from Madiun. The variables of this research are several criteria for selecting batik which consist of batik motifs, batik colors, batik prices, and types of batik fabrics. The instrument used in this study was a questionnaire. In this case, filling out the weighting questionnaire is done by using a measurement scale in the form of a semantic differential by Osgood. The data analysis technique of this research was carried out using the Analytical Hierarchy Process (AHP) method. The results of this study the most influential criteria in the selection of Madiun batik produced by MSMEs in Madiun City are the price criteria, after that the color, then the type of fabric, and finally the motif criteria. Based on the color criteria, porang batik occupies the first priority. Then the best Madiun batik on the price criteria is Porang batik. For the criteria for motifs and types of fabrics, the best Madiun batik is Kenongo. The results of this study can be used as a reference so that batik craftsmen typical of Madiun pay attention to price criteria, colors, types of fabrics and motifs, so that consumers are more interested in buying the batik products offered.